تدابیر قانون حمایة أمن الشهود والخبراء والضحایا: دراسة مقارنة - مغني، دلیلة (جامعة أحمد دراية أدرار, 2017)
The witness, as well as the informer, renders a service to justice by their testimony on the criminal offenses of which they have taken knowledge of. The judicial expert also puts his knowledge in the disposal of justice. But a testimony involves the risk of exposing its author to reprisals on his person or his entourage. For this reason, the State is in the obligation to ensure him or her (witness and informer) an effective protection which can be criminal, procedural or both during the entire period prior to their presentation before the court and subsequent to their statements. Algeria has responded to this obligation and has preserved it in the Act n 15-02 supplementing the Criminal Procedure Code by chapter six including the provisions relating to the protection of witnesses, experts and victims.
يقدم الشاهد أو المبلغ خدمة عامة للعدالة بمساعدته القضاء عن طريق الإدلاء بشهادة صادقة عن ما وقف عليه عن طريق حواسه من معلومات تتعلق بجريمة وقعت، كذلك الحال بالنسبة الخبير الذي يقدم آراء وتقييمات وأحكام توصل إليها بتطبيق قوانين علمية أو أصول فنية، لذلك يقع على الدولة في المقابل واجب توفير مختلف صور الحماية الفعالة لهؤلاء سواء الموضوعية أو الإجرائية أو الأمنية خلال الفترة السابقة على مثلوهم أمام المحكمة واللاحقة على الإدلاء بشهادته أو بلاغه أو خبرته، وهو ما استجابة له الجزائر وكرسته في الفصل السادس من الباب الثاني من الكتاب الأول من القانون رقم 15-02 المتمم والمعدل لقانون الإجراءات الجزائية، والذي جاء تحت عنوان "في حماية الشهود والخبراء والضحايا".
Keywords: القانون الجزائري -- الحماية القانونية -- الإجراءات الجزائية -- شهادة الشهود -- الاتفاقيات الدولية